e-Governance in Africa From Theory to Action - Gianluca C. Misuraca (AFRIKA WORLD PRESS, 2007)
Information and Communication Technologies (ICTs) are bringing about major changes in the way in which local and regional authorities operate, interact and communicate internally or with other administrations, enterprises and citizens. As the closest level of government to the citizen and the main providers of public services, local and regional authorities are in the front line in the development of e-government and e-governance initiative. e-government can be defi ned in many ways, but this work identifi es it as the composite trend of governments at all level, mainly through their operational arm, the administration and, subsidiarily through the access of citizens to public aff airs, aimed at promoting 1) a better and more effi cient administration, 2) more eff ective inter-administration and administration-enterprise relationships and 3) user-empowering servicing and more transparent access of citizens to political decision-making. e-governance is instead generally referred to as the capacity of ICTs to harness changes, looking not only at the increasing use of ICTs as a technological tool for delivering services online and improving the effi ciency of administrations, but as a new paradigm for opening up government services to citizens, thereby increasing transparency and participation, and making government more responsive and centred upon its citizens’ needs.